PALAEODINOPHYSIS GEN. ET SP.N. FROM THE DEVONIAN OF THE RUDNYY ALTAY (A UNIQUE FIND OF DINOFLAGELLATE FOSSILS) - Vozzhenikova T.F.; Sheshegova L.I. (My University, 1989)
While studying acritarchs from the Rudnyy Altay, we the authors discovered one cyst of a dinophyte alga whose structure provides evidence for its taxonomic membership in the order Dinophysiales. Morphologically, the cyst resembles present-day organisms of the genus Dinophysis. Since this cyst shows an antapical proturberance, it resembles Dinophysis caudata. This is the first find of a representative of the Dinophysiales, as until now fossil cysts of this order have been found. Dinoflagellate cysts are abundantly and diversely represented in the Mesozoic and Cenozoic, but until now only one genus and one species, Arpilorus antiquus, from the deposits of the Upper Silurian in Tunisia, was known in the Paleozoic. Palaeodinophysis altaica from the Devonian of the Rudnyy Altay is the second find of a dinoflagellate cyst. The description of the new genus and species is presented in this paper.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская